El autobus magico en el fondo del mar - Cole, Joanna; Degen, Bruce (New York : Scholastic, 1993)
On another special field trip on the magic school bus, Ms. Frizzle's class learns about the ocean and the different creatures that live there.
"Mariposa, Scholastic en espanol."
Translation of: The magic school bus on the ocean floor.
Accelerated Reader
Keywords: Marine animals -- Juvenile literature; Ocean bottom -- Juvenile literature; Animales marinos -- Literatura juvenil; Océano -- Literatura juvenil